Hatchlings of the Marine Turtle Lepidochelys olivacea Display Signs of Prenatal Stress at Emergence after Being Incubated in Man-Made Nests: A Preliminary Report - Herrera-Vargas, Ma. A.; Meléndez-Herrera, Esperanza; Gutiérrez-Ospina, Gabriel; Bucio-Piña, Fany E.; Báez-Saldaña, Armida; Siliceo-Cantero, Héctor H.; Fuentes-Farías, Alma L. (Frontiers in Marine Science, 2017)
Egg translocation and incubation in man-made nests (MMN) are common conservation practices through marine turtle hatcheries worldwide. These measures have been associated with reduced hatching rates, altered hatchling sex ratio, fetal dysmorphic anatomical features, and feeble hatchlings health. Previous studies have shown that MMN and natural nests (NN) provide different incubatory conditions. Therefore, incubatory challenges imposed by MMN conditions on fetal development could induce stress responses affecting hatchlings functional morphology later on life. There is no evidence of incubatory stress associated with conservation measures in turtle fetuses or hatchlings. Thus, in this paper we tested the hypothesis that MMN incubation exposes turtle fetuses to stressing conditions. Given that the hypothalamic-pituitary-interrenal axis begins functioning by day 11 of incubation in reptiles, our experiments explored the effects of incubatory conditions, rather than those associated with translocation, on fetal stress responses. We showed that Lepidochelys olivacea hatchlings incubated in MMN displayed reduced body weight, hypertrophic inter-renal glands, testicular hypotrophy and hypotrophic dorso-medial cortical pyramidal neurons, when compared with hatchlings emerging from NN. Furthermore, MMN hatchlings had higher serum levels of corticosterone at emergence, and displayed an attenuated acute stress response after traversing the beach. Therefore, the relocation of nests to protect them could negatively impact the health and survival of sea turtles. Thus, this action should only be undertaken when no alternative is available.